RANCANG BANGUN SISTEM INFORMASI PENGADAAN PROPERTI SEKOLAH BERBASIS WEB - Beethoven; Amrizal (Computer Science and Industrial Engineering, 2022)
Private schools are today subject to intense rivalry; those without a sufficient system will fall behind their rivals. The deployment of new information and systems in the procurement division, or typically the warehouse section, which serves to help facilitate checking and procurement of property in this warehouse division, is one area where we follow recent technology. The Sekolah Globe National Plus in Batam, which had been operational for twelve years, served as the site for the author's investigation. The author employs the SDLC Waterfall approach to conduct this research; the method is frequently referred to as a design method and is used to create applications that are frequently used; in this article, the author also includes a diagram design step.